2020
DOI: 10.1111/ijcp.13852
|View full text |Cite
|
Sign up to set email alerts
|

Waterpipe smoking, internet addiction and depression: A public health problem trio?

Abstract: Background Waterpipe smoking and Internet addiction may result in a new public health problem globally. This study aimed to explore waterpipe use among a large group of adolescents and its association with Internet use, mental health, primarily depression and their demographic characteristics. Methods Using a stratified random sampling method, 2054 tertiary school students aged 14‐18 years were recruited in 2019. Demographical information and use of tobacco products (eg, waterpipe) were explored and compared w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…A positive and low-level significant relationship was found between students' internet use locations, internet usage frequencies, and internet addictions in a study done by Tuncalp [34]. Adolescent internet addiction was found to be positively connected with smoking, psychological problems, computer time, smartphone usage time, and playing digital games [35][36][37][38][39]. Playing games on the internet has become one of the important entertainment tools which triggers internet use in Turkey [40].…”
Section: The Internet Addiction In Turkish Adolescents and Its Contributorsmentioning
confidence: 99%
“…A positive and low-level significant relationship was found between students' internet use locations, internet usage frequencies, and internet addictions in a study done by Tuncalp [34]. Adolescent internet addiction was found to be positively connected with smoking, psychological problems, computer time, smartphone usage time, and playing digital games [35][36][37][38][39]. Playing games on the internet has become one of the important entertainment tools which triggers internet use in Turkey [40].…”
Section: The Internet Addiction In Turkish Adolescents and Its Contributorsmentioning
confidence: 99%
“…Results from the current study showed that parents with poor mental health smoked more cigarettes and narghile than those with good mental health. Consistently, several studies on PLOS GLOBAL PUBLIC HEALTH youth and adults have found significant associations between poor mental-health and increased use of narghile [38][39][40][41][42] and cigarette smoking [43,44] compared to non-users of each method. The association between mental-health and smoking seems to be bidirectional.…”
Section: Plos Global Public Healthmentioning
confidence: 57%
“…Many studies have found that depression among university students is associated with their lifestyle behaviors. According to these studies, behaviors such as cigarette smoking, hookah smoking, alcohol use, less healthy lifestyle habits, poor sleep quality, and internet addiction are associated with depressive symptoms (5)(6)(7)(8)(9). In addition, interventions that improve lifestyle play a role in reducing students' depressive symptoms (10).…”
Section: Introductionmentioning
confidence: 99%